Contestation Between Islamic Law and Patrilineal Traditions: Insights from the Toba Batak Community - Hutagalung, Syahrial Arif; Rambe, Mara Sutan; Aripin, Jaenal; Naldo, Jufri; Tarigan, Azhari Akmal (Media Syari'ah, 2024)
The purpose of this study is to examine how the Toba Batak Muslim community maintains its cultural identity in the face of complex dynamics while adapting to Islamic principles in the face of urbanization and economic change by examining the pattern of relationships between Islamic law and customary traditions. Three regions—traditional rural areas (Humbang Hasundutan, Tapanuli Utara, Samosir, Toba), multireligious communities (Asahan, Tanjung Balai, Labuhanbatu), and large cities (Medan, Bandung)—are the focus of this qualitative study using a case study methodology. The study's findings highlight three key trends in the interaction between Islam and customs: harmony, compromise, and adaptation. The adaptation trend is evident in individuals from the place of origin who endeavor to maintain practices with minimal impact from Islamic law. A negotiation pattern has developed among individuals in diverse religious contexts who want to reconcile local customs with Islamic principles. Simultaneously, a pattern of harmony is observed in metropolitan areas, where individuals successfully reconcile traditions with Islamic tenets within a contemporary framework. Economic conditions and social mobility significantly influence these trends. Individuals with superior economic advantages often prioritize religious ideals, whereas others with economic constraints rely more on customs as a social mechanism. Social mobility facilitates the adaptation of traditional values to be more flexible and inclusive of Islamic beliefs, particularly in metropolitan settings. This study suggests that economic factors and social mobility act as catalysts in transforming the link between customs and religion within the Toba Batak Muslim community. Research recommendations emphasize the significance of locally-based religious education, inclusive discussion between indigenous and religious leaders, and economic empowerment to foster harmony between traditional beliefs and Islam.